IMPROVEMENT IN SYMPTOMS OF GAUCHER'S DISEASE BY CEREZYME - Mazher, Wajida; Ali, Jamshed; Abubakar, Saadia; Basar, Saqib; Murtaza, Ghulam (Journal of Ayub Medical College Abbottabad, 2018)
Gaucher's disease is the most common lysosomal storage disease which occurs due to a deficiency of the enzyme glucocerebrosidase. This enzyme deficiency leads to accumulation of glucocerebrosidase in the cells of macrophage-monocyte system. It is inherited as an autosomal recessive mutation and has three clinical subtypes. The disease presents with anaemia, hepatosplenomegaly, skeletal disorders and organ dysfunction. We present the case of an 18-month old male child who had presented to Civil Hospital, Karachi with fever, progressive pallor, abdominal distention for 6 months and was diagnosed as a case of type 1 Gaucher's disease on the basis of low leukocyte glucocerebrosidase activity, raised plasma chitotriosidase and the presence of Gaucher cells on bone marrow biopsy. The disease was treated with Intravenous replacement of the enzyme Imiglucerase (cerezyme) and the patient was followed. An informed Consent of the parents was taken prior to the writing of the manuscript. Keywords: Gaucher Disease; Imiglucerase; Enzyme Replacement therapy